ACHIEVING WORK FAMILY BALANCE (WFB) AMONG PROFESSIONAL WORKING WOMEN IN MAURITIUS: A QUALITATIVE STUDY - Nishaat, Beebeejaun (PEOPLE: International Journal of Social Sciences, 2017)
The role of women in Mauritius is changing rapidly mainly due to industrialisation where a major influx of women were been absorbed by the Export Processing Zone (EPZ) sector during the 1980’s. Although Mauritian women were primarily recruited for cheap labour, their employment gave them a certain degree of professional and social freedom. These women are now more present in the professional world due to their high qualifications and performance at work. However, while they are spending longer hours outside the home, their domestic responsibilities have not lessened. In Mauritius, given the nature of its patriarchal society, it is widely accepted that women should play an active role in the professional world while still handling family matters without jeopardising the family equilibrium. This qualitative study aims at understanding how women juggle, to face both professional and personal lives. Fifteen in-depth semi-interviews were conducted among women academics in different tertiary institutions around Mauritius and the data was analysed thematically. Findings showed that the most common challenges faced by working women are stress and fatigue, low support systems, time management issues, childcare issue, and their work schedule. Professional women feel burdened by coincident demands of their career aspirations and the traditional way of life. The study can help in reducing Work Family Balance (WFB) among women professionals.